Validation of a [3H]Astemizole Binding Assay in HEK293 Cells Expressing HERG K+ Channels - Peter J.S. Chiu; Karen F. Marcoe; Sidney E. Bounds; Chun-Hsiung Lin; Jin-Jye Feng; Atsui Lin; Fong-Chi Cheng; William J. Crumb; Richard Mitchell (Elsevier, 2004)
A radioligand binding assay for the HERG (human ether-a-go-go-related gene) K+ channel was developed to identify compounds which may have inhibitory activity and potential cardiotoxicity. Pharmacological characterization of the [3H]astemizole binding assay for HERG K+ channels was performed using HERG-expressing HEK293 cells. The assay conditions employed yielded 90% specific binding using 10μg/well of membrane protein with 1.5 nM of [3H]astemizole at 25°C. The Kd and Bmax values were 5.91 ± 0.81 nM and 6.36 ± 0.26 pmol/mg, respectively. The intraassay and interassay variations were 11.4% and 14.9%, respectively. Binding affinities for 32 reference compounds (including dofetilide, cisapride, and terfenadine) with diverse structures demonstrated a similar potency rank order for HERG inhibition to that reported in the literature. Moreover, the [3H]astemizole binding data demonstrated a rank order of affinity that was highly correlated to that of inhibitory potency in the electrophysiological studies for HERG in HEK293 (rSP = 0.91, P<0.05). In conclusion, the [3H]astemizole binding assay is rapid and capable of detecting HERG inhibitors. Keywords:: HERG, radioligand binding, astemizole, long QT syndrome, K+ channel